APPLICATION OF TWO TYPES OF COOPERATIVE LEARNING MODEL TWO STAY TO STRAY TO IMPROVE STUDENT LEARNING OUTCOMES IPS PGSD UNIMED - Herawaty Bukit, Masta Ginting, (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2015)
The problem in this research is the low student learning outcomes in social studies. This research aims to improve learning outcomes Students Cooperative model with Type Two Stay Two Stray. The population in this study is the Student PGSD FIP UNIMED to amount to 34 people. Data collection techniques performed in two cycles, with each cycle consisting of four stages: planning, action, observation and reflection. The results obtained show that the learning outcomes of Supreme Student PGSD FIP UNIMED implemented using two stay two stray is the complete 20 people with a percentage of 58.83% who did not complete 14 people with a percentage of 41.17%. At the end of the test on the second cycle obtained 32 with the percentage of 94.11% which is thoroughly studied and incomplete 2 with a percentage of 5.89%. In this case in accordance with the indicators of success of 100% action.Â Keywords: Cooperative Learning, Learning Outcomes